Emerging Trend of Oral and Oropharyngeal Squamous Cell Carcinoma in Patients Less than 40 Years: A Molecular Analysis of Role of HPV in Cases with No Known Risk Factors - Priyanka Nair; Usha Hegde; Sreeshyla Huchanahalli Sheshanna; Sunila Ravi (Wolters Kluwer Medknow Publications, 2022)
Introduction: Traditional risk factors causing oral and oropharyngeal cancers have been extensively studied in elderly populations. But recent evidences have shown it to be rising in young individuals with no known risk factors. Human Papilloma virus (HPV) is a proven etiologic factor for cervical cancer and has been suggested in oral squamous cell carcinoma (OSCC) and oropharyngeal squamous cell carcinoma (OPSCC). Hence the objective of the study was to evaluate the role of HPV as a risk factor in OSCC and OPSCC patients of less than 40 years of age without known risk factors. Material and Methods: Fifteen years of retrospective data were used for recording the age, gender, site, and various risk factors in patients ≤40 years of age diagnosed histopathologically with primary OSCC and OPSCC. Role of HPV in patients without any known risk factors were evaluated with p16 Immunohistochemistry (IHC) and polymerase chain reaction (PCR). Results: Ninety eight patients aged ≤40 years of age were obtained with known and no known risk factors. Among the habitual risk factors, alcohol did not prove to be a significant factor. Female patients with mean age of 34 years were more prone, though they were not subjected to any of the known risk factors. Tongue and buccal mucosa were the most common sites affected. Role of HPV as a risk factor was found positive. All cases of PCR positive were IHC positive and IHC showed 100% sensitivity and 68.4% specificity. Conclusion: A strong correlation of HPV with OSCC and OPSCC in adults ≤40 years of age was established in the present study.